Postural Differences in Speaking Versus Non-Speaking Children with Autism Spectrum Disorder - Marta Będziechowska-Czyżewska; Roksana Malak; Mateusz Romanowski; Mirosław Andrusiewicz; Włodzimierz Samborski; Ewa Baum (Children)
Background/Objectives: Autism spectrum disorder (ASD) is a heterogeneous condition with diverse symptoms influenced by factors like gender, severity and the involvement of family and therapists. While many risk factors that contribute to ASD development are known, the exact etiology remains unclear. The relationship between speech ability and postural/gait patterns in ASD has not been extensively studied. This study aimed to verify if the ability to speak can affect body posture and gait patterns. Methods: The study involved 28 boys aged 6–17. The postural assessment used the Adams test, Bunnell scoliometer, goniometer, and inclinometer to measure trunk rotation, joint range of motion, and spinal curvature. Trunk muscle strength was assessed via a flexion test measuring position maintenance time. This study compare body posture parameters in speaking and non-speaking children with Autism Spectrum Disorders. Moreover the parameters were compared to the general norms. Results: The study observed a tendency for speaking children to deviate more from normative body posture. They presented shoulder protraction more often, increased lumbar lordosis angle, and anterior pelvic tilt. Additionally, non-speaking children were more prone to toe-walking, which, according to other studies, is present in approximately 8–9% of all children with autism spectrum disorders. Both groups presented a decreased angle of dorsal flexion in the ankle joint. Conclusions: This study suggests that speaking children with ASD exhibit greater anterior-posterior postural deviations (increased lumbar lordosis, shoulder protraction, anterior pelvic tilt) than non-speaking children. ASD did not affect scoliosis or trunk rotation. Non-speaking children showed a higher incidence of toe-walking. However, the small sample size limits the generalizability of these findings.